Cladocerans of genus Alona Baird, 1843 (Cladocera: Anomopoda: Chydoridae) and related genera from Aguascalientes State, Mexico - Sinev, Artem Y.; Silva-Briano, Marcelo (Zootaxa, 2012)
Eight cladoceran species of Alona s. lato and related genera were found in Aguascalientes state, Mexico, after extensivesampling efforts. Two of them are new for science. Both new species belong to the pulchella-group of Alona and sharedistinctive features of the group. Alona aguascalientensis sp. nov. differs from the other species of the group by thepresence of denticles on posteroventral corner of valves, by a moderately elongated narrow postabdomen with weaklyprotruding distal angle and postanal marginal denticles of the same size, and by the morphology of major head pores, withconnection between central and posterior pores always absent, while connection between anterior and central porespresent or interrupted. A. anamariae sp. nov. differs from the other species of the group by the long last seta in the anteriorgroup of setae of the ventral margin of valves, by short, relatively wide, evenly narrowing distally postabdomen, and bythe small size (it is the smallest species of the group). Both new species seems to be endemic of Central Mexican Plateau.Other species found are A. glabra Sars, 1901, A. cf. guttata Sars, 1862, A. ossiani Sinev, 1908, A. setigera Megard, 1967, Coronatella circumfimbriata (Megard, 1967) and Leberis davidi (Richard, 1895).